Supervisi Edukatif Kolaboratif Untuk Meningkatkan Kinerja Guru Di SDN Jogoroto Jombang - Fauziah, Nur (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is the implementation of supervision in improving teacher performance. Fun and meaningful learning is formed through the teacher's commitment in developing his performance. A teacher must always improve his professional abilities, knowledge, attitudes and skills continuously according to the development of science and technology including the new paradigm of education. The reality in the field of teachers in Jogoroto Jombang State Elementary School has low performance and insight. This is due to (1) low awareness of teachers to learn, (2) lack of opportunities for teachers to participate in training, both regionally and nationally, (3) the lack of effective PKG, (4) educational supervision aimed at improving the learning process tends to focus on administrative aspects. For the improvement of these conditions through collaborative educational supervision that is carried out periodically. This study uses action research with the number of classroom teacher subjects in SDN Jogoroto Jombang as many as 8 teachers. The research time is in the 1st semester of the 2019-2020 study year. Data collection uses observation and documentation. The results showed that the steps taken in collaborative supervision were as planned and the results were good.